Underground Front : The Chinese Communist Party in Hong Kong - Loh, Christine (Book collections on Project MUSE.)
Underground Front is a pioneering examination of the role that the Chinese Communist Party has played in Hong Kong since the creation of the Party in 1921, through to the present day. This book brings events right up to date and includes the results of a survey about the Hong Kong public's attitude towards the CCP. The numerous appendices on the key targets of the party's united front activities also make it an especially useful read for all who are interested in Hong Kong history and politics, and readers who are interested in the history of modern China.